Competencia Comunicativa Intercultural en Español como Lengua Extranjera (ELE): Experiencia de una Sinoparlante en Colombia (2022)
This research document offers information related to the process and results of a case study that aimed to investigate the cultural aspects that favored or inhibited the learning of ELE by a Chinese speaker in Colombia. The research was carried out en el semillero de investigadores PROPONELE de la Facultad de Educación de la Universidad Antonio Nariño. The information was collected by a semi-structured interview and a field diary, and its analysis was carried out through a triangulation exercise. The results obtained in the research exercise allow us to conclude that, although the inventory of cultural knowledge offered in ELE courses in China is useful for a general approach to Colombian culture, the context of immersion implies significant communication challenges for students who come from a social context with marked differences.